Synopsis of the genera of Geniatini (Coleoptera: Scarabaeidae: Rutelinae) with an annotated catalog of species - Jameson, Mary Liz; Hawkins, Shauna Joy (Zootaxa, 2005)
We provide an overview and synopsis of the 13 genera of Geniatini (Coleoptera: Scarabaeidae: Rutelinae) including keys to genera (Spanish and English), catalog, representative habitus illustrations for all genera, character illustrations, and distribution maps for each genus. We summarize the natural history, pest status, and distributional data for each genus. Diagnostic characters are provided for each genus, and generic-level relationships are discussed. We provide an annotated catalog of all taxa in the tribe with distributional data for each species. The following taxonomic changes are made: Bolax costipennis Machatschke, 1974 is a homonym and new junior synonym of B. costipennis Ohaus, 1928; Geniates panamaensis Frey, 1976 is transferred to the genus Lobogeniates (=Lobogeniates panamaensis (Frey)); Geniates lindemannae Frey, 1976 is transferred to Geniatosoma Costa Lima (=Geniatosoma lindemannae (Frey)); Geniatosoma fernandezi Martínez, 1977 is a new junior synonym of Geniatosoma lindemannae Frey; and Trizogeniates caseyi Villatoro, 2002, which was created as a replacement name for a junior homonym, is an unavailable name.Proveemos una síntesis y sinopsis de los 13 géneros de Geniatini (Coleoptera: Scarabaeidae: Rutelinae) incluyendo claves para los géneros (español y inglés), un catálogo, ilustraciones representativas del habitus para todos los géneros, ilustraciones del carácteristicas, y mapas de la distribución para los géneros. Resumimos la historia natural, estatus como especies plagas y datos de distribución de cada género. Se proveen los caracteres diagnósticos para cada género y las relaciones entre géneros son discutidas. Proveemos un catálogo anotado para todos los taxa de la tribu y datos de distribución par cada especie. Los siguientes cambios nomenclaturales fueron hechos: Bolax costipennis Machatschke, 1974 es un homónimo sinónimo menor de B. costipennis Ohaus, 1928; Geniates panamaensis Frey, 1976 es transferido al género Lobogeniates (=Lobogeniates panamaensis (Frey)); Geniates lindemannae Frey, 1976 es transferido al género Geniatosoma Costa Lima (=Geniatosoma lindemannae (Frey)); Geniatosoma fernandezi Martínez, 1977 es un nuevo sinónimo menor de Geniatosoma lindemannae Frey; y Trizogeniates caseyi Villatoro, 2002, que fue creado como nombre de reemplazo para un homónimo menor es un nombre inválido.